Application of the 45° Semi-Fowler Position and Pursed Lip Breathing in STEMI Patients with Ineffective Breathing Pattern: A Case Study - Muhammad Fahrul Farizqi; Indah Dwi Pratiwi (Asosiasi Dosen Muda Indonesia, 2026)
ST-Elevation Myocardial Infarction (STEMI) is a cardiovascular emergency caused by complete occlusion of a coronary artery, which may result in myocardial ischemia, decreased cardiac function, pulmonary congestion, and impaired tissue oxygenation. Respiratory problems such as dyspnea, increased respiratory rate, and ineffective breathing pattern may occur in STEMI patients and require supportive nursing interventions. The combination of the 45° Semi-Fowler position and Pursed Lip Breathing is a simple non-pharmacological intervention that may help improve ventilation and oxygenation. Objective: This study aimed to describe the implementation of the combination of the 45° Semi-Fowler position and Pursed Lip Breathing in improving respiratory status among STEMI patients with ineffective breathing pattern. Methodology: This study used a descriptive nursing case study design involving two STEMI patients treated in the Intensive Cardiac Care Unit. Data were collected through direct observation of respiratory status before and after the intervention. The observed indicators were peripheral oxygen saturation (SpO₂) and respiratory rate. The data were analyzed descriptively by comparing respiratory parameters during the three-day observation period. Findings: The results showed a tendency toward improvement in respiratory status in both patients. Oxygen saturation increased from 96% to 98%, while respiratory rate decreased from 20–24 breaths per minute before the intervention to 16–20 breaths per minute after the intervention. Implications: The findings suggest that the combination of the 45° Semi-Fowler position and Pursed Lip Breathing may be used as a supportive independent nursing intervention to help improve oxygenation and reduce breathing effort in STEMI patients, without replacing standard medical therapy. Originality: This study provides a clinical description of the combined use of body positioning and breathing exercise in STEMI patients with ineffective breathing pattern, an area that remains limited in previous nursing case studies.